Personality traits and the managerial capacity of community-based facilities providing HIV services to key populations in Kenya and Malawi - Andrea Salas-Ortiz; Marjorie Opuni; José Luis Figueroa; Louis Masankha Banda; Alice Olawo; Spy Munthali; Julius Korir; Barbara Nyambura Thirikwa; Agatha Bula; Navindra Persaud; Sergio A. Bautista-Arredondo (PLoS ONE, 2026)
Community-based facilities delivering HIV services to key populations often face significant operational and financial challenges, making the quality of management in these organizations particularly important. A growing body of evidence links management quality to health facility performance. However, research on management in health facilities has focused largely on structural characteristics and formal qualifications, with less attention to the non-cognitive characteristics of managers themselves, particularly personality traits. This is a cross-sectional, quantitative analysis of 45 facilities providing HIV services to key populations in Kenya and Malawi. The analysis includes two stages. We first use k-means cluster analysis on management practice data to identify sub-groups of facilities that share similar management profiles. We then use non-linear logit regression models to predict the probability of facilities belonging to each sub-group as a function of manager personality traits, controlling for manager education, experience, and facility location characteristics. We used the Big Five Inventory to measure personality traits. We found two clusters of facilities with statistically different levels of managerial capacity. The higher-capacity cluster shows stronger financial and people management, more developed performance monitoring and target setting, better operations management, and greater community involvement in financial decisions. In the non-linear logit models, educational achievement was not statistically significant. Manager experience working with HIV key populations and higher scores on the Stability meta-trait were positively and significantly associated with the probability of belonging to the high-managerial capacity cluster. The personality traits of managers, together with their technical and cognitive skills, are relevant to the selection and support of managers in these organizations.